Hospitalization of the newborn, puerperium and maternal needs: nursing implications - Ramírez Robles, Marisol (2025)
Talking about the hospitalization of a newborn is a complex process, although the care of the newborn is guaranteed in the neonatal unit. Who guarantees the well-being of the mother of the hospitalized newborn during their stay in the neonatal unit? and especially during her postpartum period; which can be physiological or surgical with or without complications, who provides holistic care to help make the transition of this process more bearable? Her physical, emotional and psychological recovery, added to the hospitalization of her newborn child, create an imbalance in her well-being. Therefore, nursing professionals and/or a multidisciplinary health team must provide care to the mother of a newborn hospitalized in the neonatal unit, because the mother, in addition to experiencing the postpartum process, may experience suffering when leaving her child hospitalized. Given this, the objective arises to reflect on the implications for nursing caused by the hospitalization of the newborn, the postpartum period and the maternal needs to mitigate their suffering.